The role of marketing mix and social media strategies in influencing international students’ university choices in Jordan - Al-Dmour, Rand; Al-Dmour, Hani; Al-Dmour, Ahmed (Journal of International Students, 2024)
This study investigates the role of social media quality in mediating the effects of marketing mix strategies on international students’ decisions regarding their study destinations, focusing on Jordanian universities. Integrating consumer behavior theories, the research aims to understand how marketing mix elements—product/program quality, price, location, and promotional activities—impact enrollment decisions. A survey of 2000 international students recently admitted to public and private universities in Jordan yielded a 61% response rate. Empirical analysis shows that marketing mix strategies significantly impact students’ choices and elucidates the mediating role of social media strategies. Interactions on these platforms, such as reviews, ratings, and recommendations, are pivotal in forming perceptions and guiding choices, highlighting the necessity for educational marketers to manage social media content.